International demand for the Douro (Portugal) river cruises: A gravity model approach. Issue 8 (December 2017) - Gouveia, Sofia; Rebelo, João; Lourenço-Gomes, Lina; Guedes, Alexandre
Cruises on the Portuguese Douro river have been growing at a much faster pace than overall outbound tourism to Portugal, suggesting that the river is part of a worldwide trend that has been organized by global cruise operators. A gravity model is used to analyse the main factors affecting the international demand for Douro river cruising over the period from 2007 to 2014. The numbers of international passengers are positively determined by income per capita of origin country and by the population size of the leading countries of outbound tourism to Portugal.